Asociación entre hígado graso no alcohólico y colecistectomía en un hospital de Piura 2024 - Garcia Miñano, Daniel Jose (2024)
El presente estudio tuvo por objetivo determinar la asociación entre Hígado Graso no Alcohólico (HGNA) y antecedente de colecistectomía, en un Hospital de Piura. Se utilizó un muestreo no probabilístico por cuotas, conformando una muestra de 216 pacientes, con 72 casos y 144 controles. Information was collected based on clinical records, using a form that included sociodemographic, medical, and surgical information. 69.9% of the participants were women, with an average age of 45.3 years. A high prevalence of obesity (55.6%), type 2 diabetes mellitus (26.9%), frequent alcohol consumption (24.2%), and smoking (41.7%) was observed. Statistically significant associations were identified between NAFLD and nutritional status, alcohol consumption, history of cholelithiasis, and cholecystectomy (p < 0.001). The analysis revealed that obesity, frequent alcohol consumption, and history of cholelithiasis and cholecystectomy are associated with an increased risk of NAFLD. These findings highlight the importance of considering these factors in the prevention and management of NAFLD in clinical practice.